Identifikasi Potensi Psikoterapi Kawruh Jiwa Ki Ageng Suryomentaram sebagai Wisata Kebugaran Berbasis Kearifan Lokal - Devi, Arundina; Maizida, Karlina (Gadjah Mada Journal of Tourism Studies, 2022)
Kawruh Jiwa Ki Ageng Suryomentaram is a local based psychotherapy originally from Yogyakarta, which is based on human feelings principally for self-introspection, hence Kawruh Jiwa means knowledge of feeling (raos). This study aims to identify whether Kawruh Jiwa Psychotherapy has the potential to become a wellness tourism attraction and if so, what potential does Kawruh Jiwa Psychotherapy have. This research is a qualitative descriptive study and data collection is gathered through interviews, observation, and literature study in 2021. The potential for wellness tourism in Kawruh Jiwa Psychotherapy is identified based on seven wellness tourism variables in the Extended Wellness Model (Mueller and Kaufmann, 2001), and supporting data is obtained through students' perceptions of mental health issues. The results obtained from this study indicate that Kawruh Jiwa Psychotherapy has the potential to be developed as a new wellness tourism attraction in Indonesia based on local wisdom. This study revealed that from a total of 7 variables in the wellness tourism dimension, Kawruh Jiwa Psychotherapy supports of 6 variables: Mind (mental activity, education), Body (physical fitness), Self-Responsibility, Relaxation, Social Contacts, and Environmental Sensitivity. Its potential to be one of the wellness tourism attractions in Yogyakarta surely needs support from stakeholders, especially the local government to make Dusun Balong, a location where it takes place will have more proper tourism attractions, accessibility, amenities, and ancillary (4A aspects).